Wpływ srodowiska naturalnego na kształtowanie sie oryginalnej kultury Etiopii - Gebru, Seifu (Investigationes Linguisticae, 2005)
The surrounding in a natural environment – the lay of the land, climate, soil and even plants or animals living at certain area, all that may deeply influence our behavior, though we rarely realize that. It happens that behavior of local communities is determined so much that despite living in neighboring areas they differ a lot. Obviously people living at the seaside differ in behavior and culture, and even diet, from those living in the mountains or on the desert. This fascinating phenomena of nature influences culture, history, religion, agriculture and many more domains of human life I would like to present using a remarkable example of Ethiopia. This country is not very well known. Tourism is here insignificant due to the political and economical situation. Ethiopia is usually associated with the emperor Hajle Sellasje I and great long-distance runners and famine. These stereotypes became established through the few publications on Ethiopia that have appeared in Poland. That’s why as an Ethiopian whose second motherland is Poland I would like to describe the country of my original to Polish readers.